2018
DOI: 10.1017/cem.2017.437
|View full text |Cite
|
Sign up to set email alerts
|

An environmental scan of academic pediatric emergency medicine at Canadian medical schools: Identifying variability across Canada

Abstract: This comprehensive review of academic activities in pediatric emergency medicine across Canada identifies the variability across the country, including the recognition of sites above and below the national average, which may prompt change at individual sites. Sharing these academic practices may inspire sites to provide more support to teachers, educators, and researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Similar to other environmental scans for other academic endeavours, this report provides useful baseline information for comparison and highlights areas for improvement. 21,22 On a national level, our results are guiding the CAEP QIPS committee's key strategic activities to develop recommendations and coordinate large-scale initiatives to support the growth of QIPS capacity across Canada. For example, our results revealed that a few centres were significantly more successful at producing a high volume of scholarly QIPS output; there is an opportunity for sharing successful strategies amongst all EM departments and perhaps leading to larger multicentre QIPS initiatives.…”
Section: Discussionmentioning
confidence: 94%
“…Similar to other environmental scans for other academic endeavours, this report provides useful baseline information for comparison and highlights areas for improvement. 21,22 On a national level, our results are guiding the CAEP QIPS committee's key strategic activities to develop recommendations and coordinate large-scale initiatives to support the growth of QIPS capacity across Canada. For example, our results revealed that a few centres were significantly more successful at producing a high volume of scholarly QIPS output; there is an opportunity for sharing successful strategies amongst all EM departments and perhaps leading to larger multicentre QIPS initiatives.…”
Section: Discussionmentioning
confidence: 94%